Load insensitive radio frequency amplifiers to MIMO applications - Miranda, José Pedro Oliveira (2020)
This document focuses on techniques to make a radio frequency amplifying stage insensitive to load variation. Solutions like isolators, balanced amplifiers, balanced antenna and adaptive matching system are addressed from a theoretical point of view. The class–E working in sub-optimum regime has proved to maintain its efficiency over a certain load variation condition. This switching–mode class is known to achieve high efficiencies and combined with a load insensitive behaviour, can be definitely pointed as an elegant and simple solution. This configuration is implemented and tested. A 10W GaN HEMT transistor is the active device of the amplifier and the matching networks printed in an Isola Astra substrate (_ = 3 and h = 0.76). Attaining a maximum drain efficiency of 74.3 % with 12.2 % variation and 13.9 dB of maximum gain with 1.9 dB variation, for a sweep of load resistances between 30 and 200 , the design is considered to be load insensitive according to the requirements of this dissertation.